The Sensitive General Surgery Resident: Three "Difficult Conversation" Objective Structured Clinical Examinations - John Falcone; Rene Claxton; Gary Marshall (Association of American Medical Colleges, 2013)
Abstract The objective structured clinical examination (OSCE) has proven to be a reliable and valid modality to assess the Accreditation Council for Graduate Medical Education (ACGME) Core Competencies of Interpersonal and Communication Skills as well as the ACGME Core Competency of Professionalism. This resource is a three-station OSCE used at the University of Pittsburgh Medical Center to evaluate the ability of general surgery residents to have "difficult conversations" with patients and patient family members in three unique cases. The resource has the case information, checklists for standardized patient feedback, and forms for self-evaluation by general surgery residents. Standardized patients should be professionally trained in delivering the case, and providing feedback based on the checklist. After rotating through all three cases and completing the self-evaluations, learners meet in the debriefing room to discuss the cases with a surgical faculty member in a nonstructured forum. This work is significant in that it directly addresses the ACGME Core Competency of Interpersonal and Communication Skills and the ACGME Core Competency of Professionalism. Currently, this resource is used only for formative feedback and not summative evaluations. Expansion to include other "difficult conversation" topics is an area we hope to explore with the results of resident performance. We are currently prospectively evaluating this curriculum, evaluating resident performance after implementation of didactic and skills-based content to the weekly curriculum for general surgery residents.